Transformasi Sistem Pembelajaran Agribisnis untuk Meningkatkan Kompetensi Tenaga Kerja di Wilayah Teluk Betung Tahun 2021 - Astri Shabrina; Irfan Azhari; Tika Dewi (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2021)
This community service program addresses the limited competencies of the workforce in agribusiness in Kelurahan Sukarame II, Teluk Betung Barat, Bandar Lampung. The program aims to transform the agribusiness learning system to enhance technical and managerial skills among local community members. The approach utilizes Asset-Based Community Development (ABCD) combined with experiential learning and digital marketing training to empower participants based on their local assets. The implementation involved participatory training in organic vegetable cultivation, agricultural product processing, small business management, and digital marketing over three months. The findings show significant improvements in participants’ competencies across all aspects, especially in digital marketing, leading to the emergence of community-based economic groups and increased social awareness for sustainable economic development. This program highlights the effectiveness of integrating community assets and technology to foster social and economic transformation at the grassroots level.